ANALYSIS OF JOB MANAGEMENT SYSTEMS IN THE CONTEXT GRID - Yurich, M. U. (Radio Electronics, Computer Science, Control, 2010)
In this article analysis of the most common and active at the moment Resource Management Systems (RMS) is presented. We give a lot of references to Internet-resources by which you can find more information about those RMS. As a result a summary table has been compiled that shows comparative characteristics of the considered RMS and their relationship with the currently used Maui external job scheduler. RMS position in the grid-systems software is determined and when used at the local level.